Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702287
|View full text |Cite
|
Sign up to set email alerts
|

Spatially-aware or Spatially-agnostic?

Abstract: Cross-device interaction between multiple mobile devices is a popular field of research in HCI. However, the appropriate design of this interaction is still an open question, with competing approaches such as spatiallyaware vs. spatially-agnostic techniques. In this paper, we present the results of a two-phase user study that explores this design space: In phase 1, we elicited gestures for typical mobile cross-device tasks from 4 focus groups (N=17). The results show that 71% of the elicited gestures were spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
3

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…demonstrating innovative ways of using the target technology to users in order to inspire them and let them think more generally about how to accomplish a given task [35,40]. In our case, neither working in groups of two nor demonstrating the benefit of multiple tablets (e.g.…”
Section: Reducing Legacy Biasmentioning
confidence: 90%
“…demonstrating innovative ways of using the target technology to users in order to inspire them and let them think more generally about how to accomplish a given task [35,40]. In our case, neither working in groups of two nor demonstrating the benefit of multiple tablets (e.g.…”
Section: Reducing Legacy Biasmentioning
confidence: 90%
“…Existing cross-device research has highlighted challenges in adapting DUIs for collaborative environments in real-time, including problems in testing multi-device experiences [3], user interface widget adoption [11], functional UI coordination [46], component role allocation [50], spatial awareness [42] and changes in related parallel use [19]. Addressing these challenges has given rise to the approach taken here.…”
Section: Cross Device User Interfacesmentioning
confidence: 99%
“…The concept of spatial distribution has recently been taken further by using digital devices that are combined to enable crossdevice interactions [28,29]. For example Rädle et al [28] presented HuddleLamp, a desk lamp with an included camera, that allows for seamless tracking of positions of mobile devices on a desk as well as hands working on them.…”
Section: From Paper To Interactive Devicesmentioning
confidence: 99%
“…For example Rädle et al [28] presented HuddleLamp, a desk lamp with an included camera, that allows for seamless tracking of positions of mobile devices on a desk as well as hands working on them. Results of an evaluation showed that participants are capable of working on multiple surfaces and prefer spatially-aware gestures to manage information transfer and device linkage [29].…”
Section: From Paper To Interactive Devicesmentioning
confidence: 99%